Expression of heat shock protein genes Aaehsp26, Aaehsp83 and Aaehsc70 in response to thermal stress in Aedes aegypti larvae (Dhaka University Journal of Biological Sciences, 2021)
Climate change is responsible to a certain extent for the occurrence and spread of arboviral pathogens worldwide. Temperature is one of the crucial abiotic factors influencing the physiological processes of mosquitoes. Several genes of heat shock protein (AaeHsp26, AaeHsp83, and AaeHsc70) families are known to be expressed in mosquitoes, which aid in overcoming stress induced by elevated temperature. In this study, the relative expression of heat shock protein genes has been examined using Quantitative Real-time PCR (qPCR). The temperatures used for heat shock treatment were 27(control), 37, and 42°C for 1 hour heat shock period and applied to 3rd instar larvae. Significant up-regulation has been seen at 37, and 42°C. The highest expression level, about 82.43 fold, was reported for the AaeHsc70 gene at 42°C followed by 78.36 fold for AaeHsp26 at 37°C and 4.79 fold for AaeHsp83 at 42°C. The current study has shown that HSPs are important markers of stress and may function as critical proteins to protect and enhance the survival of Ae. aegypti larvae and pupae. Biological implications of these findings could impact the vector competenciesDhaka Univ. J. Biol. Sci. 30(2): 233-241, 2021 (July)